Desain circular bench adaptif dan inklusif di Canabeans Coffee KCIC Halim, Jakarta - Novrizal Primayudha; Muhammad Daffa Brisbhanuharto; Iyus Kusnaedi; Maugina Rizki Havier (Institut Seni Indonesia Yogyakarta, 2026)
This study explores the design of a circular bench as an adaptive and inclusive public furniture solution for the transit space at Canabeans Coffee, KCIC Halim Station. Employing a Design thinking approach, the bench was developed through stages of empathy, definition, ideation, and prototyping to address user needs in terms of functionality, aesthetics, and social interaction. User surveys revealed high satisfaction with comfort and accessibility, while also uncovering varied perceptions regarding visual identity and social engagement. The circular form presents a tension between symbolic openness and spatial comfort, which is examined through the lenses of proxemics and environment-behavior studies. The study’s main contribution lies in its holistic integration of function, social meaning, and user experience in public furniture design. It recommends further evaluation through simulation and field observation, as well as exploration of alternative configurations to enhance design effectiveness in high-intensity transit environments.